Nuclear magnetic resonance spectroscopic studies of the structure and interactions between hepatitis B virus core and surface antigens with peptides - Muhamad, Azira (2014)
Hepatitis B virus (HBV) infection remains a health problem globally despite the availability of effective vaccines. There are several approaches in designing an antiviral drug based on the virus life cycle. This study focuses on two antiviral approaches. The first approach is to discover a peptide that can block the virus from entering hepatocyte cells. Previous studies have implicated HBV surface antigen (HBsAg) to be involved in the virus entry into the host cells. Thus, a specific ligand targeting the immunodominant region of HBsAg is desired in neutralizing the infectivity of the virus. In a previous study, a disulfide constrained cyclic peptide cyclo S1,S9 Cys-Glu-Thr-Gly-Ala-Lys-Pro-His-Cys (S1, S9-cyclo-CETGAKPHC) was isolated from a phage displayed cyclic peptide library using an affinity selection method against HBsAg. The cyclic peptide binds tightly to the immunodominant region on HBsAg. Consequently, this study was aimed to elucidate the threedimensional structure of the cyclic peptide and its interaction with HBsAg in silico. The solution structure of this cyclic peptide was solved using 1H, 13C,and 15N NMR spectroscopy and molecular dynamics simulations with NMRderived distance and torsion angle restraints. The cyclic peptide adopted two distinct conformations due to the isomerization of the Pro residue with one structured region in the ETGA sequence. Docking studies of the peptide ensemble with a model structure of HBSAg revealed that the cyclic peptide can potentially be developed as a therapeutic drug that inhibits the virus–host interactions. The second approach is to design a peptide based on the viral surface antigen as an inhibitor to block the viral assembly. This strategy involves interaction studies between HBV core antigen (HBcAg) and HBsAg. It is of important to understand the interactions between the two viral proteins because of their involvement in the assembly of the virus. In this study, two peptides of 25 residues long were chosen from different regions of HBsAg. The peptides, designated preS and S were ligated into pGEX-2T vector and expressed in Escherichia coli. The peptides were purified using the GSTrap FF column and the recombinant peptides were chopped off from the GST tag using thrombin. The peptides each at 2.9 kDa were detected by silver staining. However, the yield obtained after cleavage was too little to carry out further studies. As such, these peptides were synthesized chemically using Fmoc chemistry and were analyzed using NMR. The solution structures of both peptides were solved using 1H, 13C, and 15N NMR spectroscopy. Peptide preS has several structured region of β-turns at Ser7- Pro8-Pro9, Arg11-Thr12-Thr13 and Ser22-Thr23-Thr24 sequences whereas peptide S has only one structured region observed at Ser3-Asn4-His5. Both peptides contain bend-like structures surrounding the turn structures. Saturation Transfer Difference (STD) NMR experiments were performed to study the interaction of the preS and S to HBcAg. Several aromatic residues of preS and S were involved in the interaction with HBcAg, indicating their potential as antiviral agents that inhibit the virus morphogenesis. The experiments carried out on the peptides were fundamental methods in designing new antiviral agents for HBV. Promising results were obtained for each peptide, paving the way for future studies on the potential HBV peptide inhibitors.